Participatory Prospective Analysis to understand the implications of tenure reform scenarios for the forestry sector and communities in forested landscapes. - CGIAR Research Program on Policies, Institutions, and Markets (2020)
PPA has been piloted in a total of 16 sites at the municipality, district, county and other sub-national levels in Colombia, Indonesia, Kenya, Nepal, Peru and Uganda,